Estimating Asphaltene precipitation in the presence of co2 injection in oil reservoirs - 512796 Saeed Akbari; Gholamreza Zahedi, supervisor; Fakulti Kejuruteraan Kimia (2011)
Thesis (Sarjana Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2011